(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The paper substantiates the importance to teach foreign languages to the students of technical universities relying upon dialogical speech in the context of cooperative pedagogy. Retrospective review of scientific sources as for theoretical foundations of dialogical learning implementation in educational activities has been represented. The concept “educational dialogue” has been specified. Educational dialogue has been considered in terms of cooperative pedagogy as a component of personally oriented, dialogical, problem solving, and developing types of educations. Besides, the paper outlines the main initial positions as for the dialogical interaction implementation while studying foreign languages; conceptual provisions contributing to the efficient implementation of professionally oriented foreign language training in the context of cooperative pedagogy have been determined. The specified initial positions concerning implementation of an educational dialogue in the learning process have allowed determining the peculiarities of organizing a dialogical learning on the principles of cooperative pedagogy in the context of teaching foreign languages to the students of technical universities among which communicative orientation; problem-solving didactic material; situation-based educational activity, and active learning forms are singled out.